(untitled) (City: History, Culture, Society, 2019)
The article deals with the spectrum of ideas about the boundary between rural and urban cultures and outlines the mechanism of this boundary constructing. Using social constructionism theory and discourse analysis was useful for exacerbating the dichotomous interpretation of rural and urban cultures. The terminological definitions of the city and the village appear to be well established and self-evident, but attention to these basic definitions is very important for further analyses. Despite a thorough academic critique of the dichotomous understanding of the city and the village, these terms continue to refer to generalized idealized types of settlements that are inherently opposite. This means that they continue to be objects of social, academic and administrative construction, based primarily on population. The classic definition of a city by L. Wirth includes population size, density and heterogeneity. However, the presence of targeted associations and economic institutions able to respond to diverse social needs are also an important feature of the city. At the same time, the village is considered as an opposition to a city with less population, as well as less density and heterogeneity. The traditional approach links rural areas to agricultural activity, but in modern conditions, this characteristic cannot be decisive since during the twentieth century the human population has become predominantly urban and this has violated established standards. A more important feature of a village is that living in a rural area implies a specific engagement with the local community, which is determined by active involvement in social networks. Urban and rural cultures find expression in an appropriate way of life. Urbanism assumes the importance of anonymous daily contacts that are part of the urban discourse reflected in the categories of diversity, opportunity and temptation. Whereas rural discourse focuses on the value of traditions, among which the customs of neighbourhood mutual assistance are the most important.